Analisis Karakteristik dan Higiene Individu Dengan Kejadian Skabies - Devi Nuraini Ariningtyas (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2019)
Scabies is a disease caused by Sarcoptes scabiei mites. Scabies can attack humans who live in groups such as barracks, army barracks, dormitories, prison houses, Islamic boarding schools and orphanages. This study was conducted to analyze the relationship between characteristics, individual hygiene, and physical environment with the incidence of scabies in LPKA I Blitar.This article is a quantitative observational study using a cross sectional approach. The research sample was chosen randomly with simple random sampling. A total of 51 children were interviewed and received the screening of scabies. The independent variables of this study are characteristic and individual hygiene, the dependent variable is the incidence of scabies.The results of the study used Chi-square test which showed that there was a relationship between individual hygiene and the incidence of scabies p = 0.001. Sub variables that have a relationship with scabies, namely the habit of using towels together has a significance of 0,000 and the habit of borrowing clothes with a significance of 0,000. Physical environment are not related to scabies.The conclusion of this study is that the hygiene of individuals has a higher risk of scabies, especially the habit of using towels together and the habit of borrowing clothes